Assessing the effect of the Trier social stress test (TSST) on psychological and physiological measurements of Vietnamese students - Quang Lam Nguyen; Ngan Huu Phuc Nguyen; Anh Phuc Hoang Le; Bao Hoai Pham; Vy Kim Huynh; Thien Hoang Minh Cao; Dong An Bui; Khon Huynh*; Huong Thi Thanh Ha* (Vietnam Journal of Science, Technology and Engineering, 2024)
The Trier social stress test (TSST) is considered as the most appropriate standardized protocol for studying stress hormone reactivity. The TSST is distinct from other stress induction protocols in laboratory settings due to its unique ability to create a natural context that includes elements of social and psychological acute stress. However, there has been no investigation of the efficacy of the TSST among the Vietnamese population. Therefore, the purpose of this study is to examine the impact of the TSST on Vietnamese university students. A group of 10 healthy male and female volunteers underwent the TSST protocol, and self-reported values (the positive and negative affect schedule and the visual analogue scale) as well as physiological stress response (heart rate) were measured. The results suggest that the TSST mildly induces acute psychological stress among Vietnamese participants. To enhance the potency of the TSST in future studies, a larger sample size and more consistent adherence to the TSST protocol are crucial.